Democracy's guardians a history of the German Federal Constitutional Court, 1951-2001 - Collings, Justin (Oxford University Press, 2015)
Consolidation, 1951-1959 -- Confidence, 1959-1971 -- Confrontation, 1971-1982 -- Continuity, 1982-1990 -- Karlsruhe Republic, 1990-2001 -- Epilogue: the view from Europe